O uso de B4C como aditivo de sinterização de SiC-Si3N4 visando o aumento da resistência à oxidação - Martin, Diego Rodrigues (2010)
In order to fulfill modern market requirements based on increased search for SiC Si3N4 products with high performance and good cost/benefit ratio, there is a natural need for additives able to sinter as well as decrease the inherent oxidation tendency of this products. Refractories based on SiC Si3N4 present several important thermal and mechanical properties at high temperatures which lead them to be used as sagars and overall furnace furniture. However carbides and nitrides including SiC Si3N4 are instable at high temperatures in air. The formation of a surface silica layer and other intergranulary distributed silicates, may function as oxidation protection. However, at the same time at high temperatures the thermal and mechanical properties can be badly affected. Based on these assumptions in this work it is presented a study involving the effect of boron carbide as a sintering and antioxidant protector on SiC Si3N4 used mainly kiln furniture. The results indicate that the use of boron carbide was very effective on fulfilling both requirements that is as sintering additive and anti oxidant.